The Urgency Of Criminalizing Illicit Enrichment And The Prospect Of Its Law Enforcement In Indonesia - Fitri Maharani; Hanafi Amrani (Fakultas Hukum Universitas Islam Indonesia, 2024)
The UNCAC has regulated illicit enrichment in Article 20 as the acquisition of improper assets by public officials whose legitimate origin cannot be proven. Indonesia has ratified the convention, which imposes a mandatory obligation to regulate illicit enrichment as a criminal offense. However, until now, Indonesia has not yet criminalized illicit enrichment. This study aims to determine the urgency of criminalizing illicit enrichment and the prospects for its law enforcement in Indonesia. This research is normative legal research with descriptive qualitative data analysis. The results of this study show that the criminalization of illicit enrichment is important to do because of international obligations as a logical consequence of the ratification of UNCAC. Furthermore, the criminalization of illicit enrichment is an effort to reform the law, especially anti-corruption law enforcement in Indonesia, including the optimization of asset recovery mechanisms. The prospect of law enforcement that can be projected for the criminalization of illicit enrichment can be studied through the perspective of material criminal law which requires delict and sanction arrangements, as well as in the perspective of formal criminal law, which requires the LHKPN report as initial evidence, the application of reversal burden of proof, and NCB asset recovery.